Characterization of NT‐proBNP in a large cohort of COVID‐19 patients. (1st February 2021) - Caro‐Codón, Juan; Rey, Juan R.; Buño, Antonio; Iniesta, Angel M.; Rosillo, Sandra O.; Castrejon‐Castrejon, Sergio; Rodriguez‐Sotelo, Laura; Martinez, Luis A.; Marco, Irene; Merino, Carlos; Martin‐Polo, Lorena; Garcia‐Veas, Jose M.; et al.
Abstract: Aims: Extensive research regarding the association of troponin and prognosis in coronavirus disease 2019 (COVID‐19) has been performed. However, data regarding natriuretic peptides are scarce. N‐terminal pro B‐type natriuretic peptide (NT‐proBNP) reflects haemodynamic stress and has proven useful for risk stratification in heart failure (HF) and other conditions such as pulmonary embolism and pneumonia. We aimed to adequately characterize NT‐proBNP concentrations using a large cohort of patients with COVID‐19, and to investigate its association with prognosis. Methods and results: Consecutive patients with confirmed severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection and available NT‐proBNP determinations, from March 1st to April 20th, 2020 who completed at least 1‐month follow‐up or died, were studied. Of 3080 screened patients, a total of 396 (mean age 71.8 ± 14.6 years, 61.1% male) fulfilled all the selection criteria and were finally included, with a median follow‐up of 53 (18–62) days. Of those, 192 (48.5%) presented NT‐proBNP levels above the recommended cut‐off for the identification of HF. However, only 47 fulfilled the clinical criteria for the diagnosis of HF. Patients with higher NT‐proBNP during admission experienced more frequent bleeding, arrhythmias and HF decompensations. NT‐proBNP was associated with mortality both in the whole study population and after excluding patients with HF. A multivariable Cox model confirmed that NT‐proBNP was independently associated with mortality after adjusting for all relevant confounders (hazard ratio 1.28, 95% confidence interval 1.13–1.44, per logarithmic unit). Conclusion: NT‐proBNP is frequently elevated in COVID‐19. It is strongly and independently associated with mortality after adjusting for relevant confounders, including chronic HF and acute HF. Therefore, its use may improve early prognostic stratification in this condition. Abstract : NT‐proBNP is frequently elevated in patients with COVID‐19 and is strongly associated with myocardial injury and all‐cause mortality.